Autologous stem cell transplantation for untreated transformed indolent B‐cell lymphoma in first remission: an international, multi‐centre propensity‐score‐matched study. (16th October 2020) - Chin, C. K.; Lim, K. J.; Lewis, K.; Jain, P.; Qing, Y.; Feng, L.; Cheah, C. Y.; Seymour, J. F.; Ritchie, D.; Burbury, K.; Tam, C. S.; Fowler, N. H.; et al.
Summary: High‐dose chemotherapy (HDC) and autologous stem cell transplantation (ASCT) are used as consolidation in first remission (CR1) in some centres for untreated, transformed indolent B‐cell lymphoma (Tr‐iNHL) but the evidence base is weak. A total of 319 patients with untreated Tr‐iNHL meeting prespecified transplant eligibility criteria [age <75, LVEF ≥45%, no severe lung disease, CR by positron emission tomography or computed tomography ≥3 months after at least standard cyclophosphamide, doxorubicin, vincristine and prednisolone with rituximab (R‐CHOP) intensity front‐line chemotherapy] were retrospectively identified. Non‐diffuse large B‐cell lymphoma transformations were excluded. About 283 (89%) patients had follicular lymphoma, 30 (9%) marginal‐zone lymphoma and six (2%) other subtypes. Forty‐nine patients underwent HDC/ASCT in CR1, and a 1:2 propensity‐score‐matched cohort of 98 patients based on age, stage and high‐grade B‐cell lymphoma with MYC, BCL2 and/or BCL6 rearrangements (HGBL‐DH) was generated. After a median follow‐up of 3·7 (range 0·1–18·3) years, ASCT was associated with significantly superior progression‐free survival [hazard ratio (HR) 0·51, 0·27–0·98; P = 0·043] with a trend towards inferior overall survival (OS; HR 2·36;0·87–6·42; P = 0·1) due to more deaths from progressive disease (8% vs. 4%). Forty (41%) patients experienced relapse in the non‐ASCT cohort — 15 underwent HDC/ASCT with seven (47%) ongoing complete remission (CR); 10 chimeric antigen receptor‐modified T‐cell (CAR‐T) therapy with 6 (60%) ongoing CR; 3 allogeneic SCT with 2 (67%) ongoing CR. Although ASCT in CR1 improves initial duration of disease control in untreated Tr‐iNHL, the impact on OS is less clear with effective salvage therapies in this era of CAR‐T.